ANALYSIS OF THE DEVELOPMENT OF MENTALLY ILL PRISONERS IN PRISONS BASED ON LAW NUMBER 12 OF 1995 CONCERNING CORRECTIONAL SERVICES - RULLY ANWARDI LUBIS; Lintje Anna Marpaung (Law Faculty of Universitas Bandar Lampung, 2022)
The Penitentiary is part of the judicial sub-system that functions as a place for people who commit criminal acts and other violations of the law to get guidance so that they can realize their mistakes and account for what they have done, one of which is in the Bandar Lampung class I penitentiary, various differences in the period of punishment make prisoners experience life pressures during the criminal period resulting in strees and disturbances mental health causes death by suicide, this research was conducted with the aim of being able to provide guidance to prisoners who experience mental health disorders in accordance with Law Number 12 of 1995, using empirical legal qualitative research methods, using a type of descriptive research analysis, the results of the study show that the coaching of mentally ill prisoners has not been optimal and has not been regulated in the law, the treatment of mentally ill inmates still receives the same rights and obligations in carrying out the sentence in the penitentiary.